Genome analysis of a halophilic Virgibacillus halodenitrificans ASH15 revealed salt adaptation, plant growth promotion, and isoprenoid biosynthetic machinery - Sharma, Anjney; Singh, Ram Nageena; Song, Xiu-Peng; Singh, Rajesh Kumar; Guo, Dao-Jun; Singh, Pratiksha; Verma, Krishan K.; Li, Yang-Rui (Frontiers in Microbiology, 2023)
Globally, due to widespread dispersion, intraspecific diversity, and crucial ecological components of halophilic ecosystems, halophilic bacteria is considered one of the key models for ecological, adaptative, and biotechnological applications research in saline environments. With this aim, the present study was to enlighten the plant growth-promoting features and investigate the systematic genome of a halophilic bacteria, Virgibacillus halodenitrificans ASH15, through single-molecule real-time (SMRT) sequencing technology. Results showed that strain ASH15 could survive in high salinity up to 25% (w/v) NaCl concentration and express plant growth-promoting traits such as nitrogen fixation, plant growth hormones, and hydrolytic enzymes, which sustain salt stress. The results of pot experiment revealed that strain ASH15 significantly enhanced sugarcane plant growth (root shoot length and weight) under salt stress conditions. Moreover, the sequencing analysis of the strain ASH15 genome exhibited that this strain contained a circular chromosome of 3,832,903 bp with an average G+C content of 37.54%: 3721 predicted protein-coding sequences (CDSs), 24 rRNA genes, and 62 tRNA genes. Genome analysis revealed that the genes related to the synthesis and transport of compatible solutes (glycine, betaine, ectoine, hydroxyectoine, and glutamate) confirm salt stress as well as heavy metal resistance. Furthermore, functional annotation showed that the strain ASH15 encodes genes for root colonization, biofilm formation, phytohormone IAA production, nitrogen fixation, phosphate metabolism, and siderophore production, which are beneficial for plant growth promotion. Strain ASH15 also has a gene resistance to antibiotics and pathogens. In addition, analysis also revealed that the genome strain ASH15 has insertion sequences and CRISPRs, which suggest its ability to acquire new genes through horizontal gene transfer and acquire immunity to the attack of viruses. This work provides knowledge of the mechanism through which V. halodenitrificans ASH15 tolerates salt stress. Deep genome analysis, identified MVA pathway involved in biosynthesis of isoprenoids, more precisely “Squalene.” Squalene has various applications, such as an antioxidant, anti-cancer agent, anti-aging agent, hemopreventive agent, anti-bacterial agent, adjuvant for vaccines and drug carriers, and detoxifier. Our findings indicated that strain ASH15 has enormous potential in industries such as in agriculture, pharmaceuticals, cosmetics, and food.